Meta-Analysis: The Effect of Waterbirth Delivery Method on the Risk of Perineal Rupture - Mayriyana Kartikasari; Lukman Aktovianta (Masters Program in Public Health, 2021)
Background: Waterbirth is the process of giving birth in a tub or pool of warm water which starts from a baby born in water and is brought to the surface. Waterbith has an effect on reducing maternal morbidity because it can have a relaxing effect and relieve pain during labor. However, the practice is still controversial in several countries. This study aimed to determine the effect of water birth method delivery with the risk of perineal rupture with a meta-analysis of primary studies linked through previous researchers.Subjects and Method: This study was a systematic review and meta-analysis study following the PICO, population: Women in labor. Intervention: Waterbirth. Comparison: other delivery methods besides water birth. Results: Perineal rupture articles used in this study were obtained from 4 databases such as Google Schoolar, Semantic Schoolar, Pubmed, and Science Direct. Keywords to search for articles including: waterbirth